Insight into the promotional mechanism of Cu modification towards wide-temperature NH3-SCR performance of NbCe catalyst - An, Dongqi; Yang, Yuyao; Zou, Weixin; Cai, Yandi; Tong, Qing; Sun, Jingfang; Dong, Lin (Chinese journal of chemical engineering, 2022)
[Display omitted] A simple strategy of Cu modification was proposed to broaden the operation temperature window for NbCe catalyst. The best catalyst Cu0.010/Nb1Ce3 presented over 90% NO conversion in a wide temperature range of 200–400 °C and exhibited an excellent H2O or/and SO2 resistance at 275 °C. To understand the promotional mechanism of Cu modification, the correlation among the “activity-structure–property” were tried to establish systematically. Cu species highly dispersed on NbCe catalyst to serve as the active component. The strong interaction among Cu, Nb and Ce promoted the emergence of NbO4 and induced more Brønsted acid sites. And Cu modification obviously enhanced the redox behavior of the NbCe catalyst. Besides, EPR probed the Cu species exited in the form of monomeric and dimeric Cu2+, the isolated Cu2+ acted as catalytic active sites to promote the reaction: Cu2+–NO3−+NO(g) → Cu2+–NO2−+NO2(g). Then the generated NO2 would accelerate the fast-SCR reaction process and thus facilitated the low-temperature deNOx efficiency. Moreover, surface nitrates became unstable and easy to decompose after Cu modification, thus providing additional adsorption and activation sites for NH3, and ensuring the improvement of catalytic activity at high temperature. Since the NH3-SCR reaction followed by E-R reaction pathway efficaciously over Cu0.010/Nb1Ce3 catalyst, the excellent H2O and SO2 resistance was as expected.